Study on the interaction of nicotinamide with sepiolite, loughlinite and palygorskite by IR spectroscopy - AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (ELSEVIER SCIENCE BV, PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS, 2005)
The adsorption of nicotinamide by two different Anatolian sepiolites (Eskisehir sepiolite and Bolu-Kibriscik sepiolite), loughlinite (Na-sepiolite), and palygorskite has been investigated using FT-IR spectrometry. The spectroscopic results indicate that nicotinamide molecules adsorbed on sepiolite, loughlinite and palygorskite are coordinated to surface hydroxyls and/or to Lewis acidic centers by hydrogen bonding interaction through the ring nitrogen lone pairs. Amino group nitrogen is found to be relatively in active to adsorbing sites. Some intensity and frequency changes in the OH stretching and deformation bands of surface hydroxyls (Si-OH) of the nicotinamide treated sepiolite and loughlinite were observed. But these bands are found to be less affected by the adsorption of nicotinamide in the case of palygorskite, probably because the surface Si-OH groups in palygorskite appear to be less abundant than in sepiolite or loughlinite. (c) 2004 Elsevier B.V. All rights reserved.
Keywords: adsorption; clay minerals; IR spectroscopy; loughlinite; nicotinamide; sepiolite; pyridine; montmorillonite; cyclohexylamine; intercalation; desorption; bentonite; anatolia; emme; kil mineralleri; IR spektroskopisi; nikotinamid; sepiyolit; piridin; montmorillonit; sikloheksilamin; ortaya ekleme; desorpsiyon; bentonit; Anadolu